Peran Bahasa dalam Komunikasi Lintas Budaya: Memahani Nilai dan Tradisi yang Berbeda - Ningrum, Ayu Condro; Tazqiyah, Izqi (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
Language plays a crucial role in intercultural communication, which occurs when individuals from different cultural backgrounds interact. Deddy Mulyana explains that cultural differences allow the message receiver to interpret information according to their understanding. Language, as an organized communication tool, not only conveys thoughts and feelings but also serves as a means of social integration and social control. Through language, individuals can express themselves, adapt to their social environment, and influence the attitudes and behaviors of others. Furthermore, understanding cross-cultural communication has become increasingly important in the era of globalization, where interactions between cultures are intensifying. This understanding includes knowledge of one’s own culture and other cultures, as well as awareness of the similarities and differences between them. By comprehending cross-cultural communication, individuals can establish better and more harmonious relationships and develop a tolerant attitude toward differences. Theories of intercultural interaction and communication emphasize the importance of factors such as actions, settings, actors, intermediaries, and goals in the communication process. Therefore, language functions not only as a communication tool but also as a bridge to understand and appreciate the cultural diversity present in society.